The Analysis Of Effectiveness Of Mobile Learning Media Usage In Train Students’ Critical Thinking Skills - Yoseb Boari; Rissa Megavitry; Petrus Jacob Pattiasina; Hasbi Taobah Ramdani; Haris Munandar (Mudir : Jurnal Manajemen Pendidikan, 2023)
The goal of this study is to provide rigid body equilibrium and rotational dynamics learning materials for mobile devices using App Inventor that are viable, efficient, and usable and that can enhance students' critical thinking abilities. This study used a 4-D development model as its research methodology, with just the development stage included in the steps of define, design, develop, and disseminate. Students in the class served as the study's subjects. Tests and non-tests (questionnaires) are the types of instruments employed. Test instruments were given to 30 students, and assessment questionnaires were given to experts (learning design, language, media, and materials), students (limited trials), and two physics teachers. The resulting media were considered appropriate by experts (learning design, language, media, and materials) and effective in training critical thinking skills with an N-gain value of 0.49 in the medium category and an educator effectiveness questionnaire with a percentage of 86% very effective category. Students rate the practicality of mobile learning material utilizing App Inventor at 78.5%, while teachers rate it at 92%.